Size Controlled Synthesis of Silicon Nanocrystals Using Cationic Surfactant Templates. Issue 3 (11th September 2013) - Linehan, Keith; Doyle, Hugh
<x xml:space="preserve">Abstract</x> Alkyl‐terminated silicon nanocrystals (Si NCs) are synthesized at room temperature by hydride reduction of silicon tetrachloride (SiCl4) within inverse micelles. Highly monodisperse Si nanocrystals with average diameters ranging from 2 to 6 nm are produced by variation of the cationic quaternary ammonium salts used to form the inverse micelles. Transmission electron microscopy imaging shows that the NCs are highly crystalline, while FTIR spectra confirm that the NCs are passivated by covalent attachment of alkanes, with minimal surface oxidation. UV‐vis absorbance and photoluminescence spectroscopy show significant quantum confinement effects, with moderate absorption in the UV spectral range, and a strong blue emission with a marked dependency on excitation wavelength. The photoluminescence quantum yield (Φ) of the Si NCs exhibits an inverse relationship with the mean NC diameter, with a maximum of 12% recorded for 2 nm NCs.